CMPK1 Regulated by miR-130b Attenuates Response to 5-FU Treatment in Gastric Cancer - Chu, Huaizhu; Han, Nahui; Xu, Jianguo (Frontiers in Oncology, 2021)
Gastric cancer (GC) remains a major world-wide challenge, especially in Asian countries. Chemotherapy with 5-fluorouracil (5-FU) and cisplatin is used as the first-line treatment and development of chemoresistance is a major cause of progression. UMP/CMP kinase is responsible for the phosphorylation of the ribonucleotide metabolite 5-fluoro-5’-monophosphate (FUMP) in 5-FU metabolic process, and recognized as a key step in the conversion of 5-FU to cytotoxic metabolites. Our bioinformatics analysis and molecular experiments demonstrated that high expression of CMPK1 was associated with prolonged survival and response to 5-FU treatment in GC samples. Further analysis demonstrated that miR-130b as a key epigenetic regulator of CMPK1, and miR-130b-mediated attenuation of CMPK1 resulted in resistance of gastric cancer cells to DNA damage and cell death after treatment with 5-FU. Rescue experiments with augmented CMPK1 expression abolished the effect of miR-130b demonstrating the key function of this miRNA in this pathway. Thus, this newly identified miR-130b-CMPK1 axis suggests a potentially new chemotherapeutic strategy for improved response to 5-FU therapy.